Competitive annealing mediated isothermal amplification (CAMP) for rapid and simple detection of Listeria monocytogenes in milk. (November 2020) - Li, Wei; Mao, Rui; Yue, Xiqing; Wu, Junrui; Wu, Rina; Qiao, Yu; Peng, Qing; Shi, Bo; Luo, Yong; Chen, Xu; Du, Yuguang
Abstract: Listeria monocytogenes ( L. monocytogenes ) is widespread in nature and considered an important foodborne pathogen. And it can cause listeriosis, which can lead to miscarriage, neonatal death, septicemia and meningitis. Therefore, the appropriate detection methods are needed to effectively control and prevent this pathogenic bacterium. Competitive annealing mediated isothermal amplification (CAMP) is a novel nucleic acid-based detection technology that amplifies DNA with high sensitivity and specificity under isothermal conditions. The aim of this study was to develop a CAMP assay for rapid and simple detection of L.monocytogenes in milk. In this system, a pair of inner primers was designed to specifically target hlyA gene of L.monocytogenes . For further optimization, loop primers and outer primers were designed to accelerate CAMP reaction. Compared with conventional PCR method, the CAMP assay has the same specificity and higher sensitivity. All 8 strains of L.monocytogenes yielded positive results using the CAMP assay and showed no cross reaction with 26 tested non -L.monocytogenes strains. The detection limit of the CAMP assay was 1.0 × 10 2  CFU/mL for pure bacterial, which was 10-fold more sensitive than PCR. Additionally, the CAMP method with the enrichment step could reliably detect L.monocytogenes in artificially contaminated milk samples at concentration as low as 1 CFU/mL. These results indicate the developed CAMP is a potential useful method for rapid detection of L.monocytogenes in milk samples. Highlights: Developed a CAMP method targeting hlyA gene for detecting L. monocytogenes. This CAMP method has high sensitivity and specificity. The CAMP with the enrichment step could reliably detect L.monocytogenes in milk at concentration as low as 1 CFU/mL.